Math, asked by info5390, 5 months ago

please tell me the answer in process ​

Attachments:

Answers

Answered by asdeepsingh777
1

Answer:

- 3/4

Step-by-step explanation:

( \frac{3}{4}  \times  \frac{8}{ - 9} ) - ( \frac{5}{6}  +  \frac{3}{ - 4} )

=

( \frac{2}{ - 3} ) - ( \frac{5}{6}  -  \frac{3}{4} ) \\  =  \frac{3}{4}  -  \frac{5}{6}  -  \frac{2}{3}

taking L.C.M:

2 | 4 — 6 — 3

2 | 2 — 3 —3

3 | 1 —3—3

| 1— 1— 1

2 ×2 ×3 = 12

so,

 \frac{3(3) - 5(2) - 2(4)}{12}

=

 \frac{9 - 10 - 8}{12}

= - 9/ 12

= - 3/4

Similar questions